Rapid separation of bacteria from blood – Chemical aspects - Alizadeh, Mahsa (2017)
To rapidly diagnose infectious organisms causing blood sepsis, bacteria must be rapidly separated from blood, a very difficult process considering that concentrations of bacteria are many orders of magnitude lower than concentrations of blood cells. We have successfully separated bacteria from red and white blood cells using a sedimentation process in which the separation is driven by differences in density and size. Seven mL of whole human blood spiked with bacteria is placed in a 12-cm hollow disk and spun at 3000 rpm for 1 min. The red and white cells sediment more than 30-fold faster than bacteria, leaving much of the bacteria in the plasma. When the disk is slowly decelerated, the plasma flows to a collection site and the red and white cells are trapped in the disk. Analysis of the recovered plasma shows that about 36% of the bacteria is recovered in the plasma. The plasma is not perfectly clear of red blood cells, but about 94% have been removed. This paper describes the effects of various chemical aspects of this process, including the influence of anticoagulant chemistry on the separation efficiency and the use of wetting agents and platelet aggregators that may influence the bacterial recovery. In a clinical scenario, the recovered bacteria can be subsequently analyzed to determine their species and resistance to various antibiotics.